Australia's new defence white paper : shifting the goal posts - Bateman, Sam (2014)
The new Australian Defence White Paper issued earlier this month re-focuses Australia’s strategic attention on its nearer region – the so-called Indo-Pacific arc. What are the implications for Australia’s regional neighbours?